A Critique of Vanessa Martin in the Book Iran between Islamic Nationalism and Secularism: The Constitutional Revolution of 1960 - Seyyed Reza Hoseini; Mostafa Rezaee; Amir Etemadi Bozorg (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2022)
Vanessa Martin is an English-speaking scholar of contemporary Iranian history who attempts to examine the Constitutional Revolution from an external perspective and its socio-political developments in her book. Therefore, the purpose of this article is to study the book analytically-critically in terms of form, method, theory and content. Vanessa Martin's focus in this book is to identify political currents and socio-economic and local developments outside of Tehran that have had a direct impact on the Constitutional Revolution and its aftermath. A review of the book shows that the author has tried to define local constitutionalism in relation to national identity. The findings show that from the author's point of view, in terms of the traditional context of Iranian society and the clergy, the constitutional revolution is considered a historical and religious issue, but intellectuals consider it a mythical and modern issue. Vanessa Martin's innovation in this book is to identify the role of local forces, especially in the regions of Azerbaijan, Bushehr, Fars and Isfahan in the Constitutional Revolution, but in the type of classification of political currents and their definition of the constitutional revolution, there are problems that need to be corrected in later versions.